The Transmission of German Monetary Policy in the Pre-Euro Period - Helmut Luetkepohl; Jürgen Wolters (Center for Economic Studies and ifo Institute (CESifo), 2001)
A small macroeconomic model is constructed to study the transmission of the monetary policy conducted by the Deutsche Bundesbank (DBB) since the middle of the 1970s. For this purpose quarterly, seasonally unadjusted data for the period from 1975 to 1998 are used, that is, the period until the introduction of the Euro is considered. A vector error correction model is constructed for the German monetary sector based on M3, GNP, an inflation rate, a long-term interest rate and a short-term rate which represents the policy variable of the DBB. Moreover, import price inflation is included as an exogenous variable to capture foreign effects. An impulse response analysis highlights the effects of changes in the short-term interest rate and shows the interaction of the main variables of the monetary sector.
Keywords: 330; cointegration analysis; impulse response analysis; monetary policy; money demand; structural vector error correction model